2022
DOI: 10.18280/ijsse.120505
|View full text |Cite
|
Sign up to set email alerts
|

Network Forensics Against Volumetric-Based Distributed Denial of Service Attacks on Cloud and the Edge Computing

Abstract: Cyber attacks are increasingly rampant and even damage the reputation of companies, agencies, and services. DDoS attacks have been overgrowing in the last year, which has resulted in substantial losses. Volumetric-based Distributed Denial of Service (DDoS) is a hazardous attack type because it can consume server resources, causing the server to be unable to serve customer requests. The network design consisting of hardware and software becomes the essential capital that is a determinant of the quality of a net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…• In an effort to counteract volumetric-based Distributed Denial of Service attacks targeting cloud and edge computing networks, Yudhana et al [13] integrated the Packet Filtering Firewall and Circuit Level Gateway Firewall. It was observed that these measures led to a substantial decline in both traffic and server resource usage, with reductions ranging between 64%-98.88% and reaching up to 96% respectively.…”
Section: Evolution Of Task Offloading Within Edge-cloud Interfacesmentioning
confidence: 99%
“…• In an effort to counteract volumetric-based Distributed Denial of Service attacks targeting cloud and edge computing networks, Yudhana et al [13] integrated the Packet Filtering Firewall and Circuit Level Gateway Firewall. It was observed that these measures led to a substantial decline in both traffic and server resource usage, with reductions ranging between 64%-98.88% and reaching up to 96% respectively.…”
Section: Evolution Of Task Offloading Within Edge-cloud Interfacesmentioning
confidence: 99%